Product innovation, product-market competition and persistent profitability in the U.S. pharmaceutical industry - Roberts, Peter W. (Strategic Management Journal, 1999)
Increasingly, strategy scholars are exploring the relationships between innovation, competition, and the persistence of superior profits. Sustained high profitability may result when a firm repeatedly introduces valuable innovations that service previously unmet consumer demands. While the returns to the firm from each innovation may erode over time, innovation ensures that, overall, the firm maintains a high performance position. At the same time, sustained high profitability may also accrue to firms that innovate less often, but effectively avoid the competition that otherwise erodes high returns. This paper elaborates these relationships before presenting an empirical analysis of the effects of differential innovative propensities and differential rates of competition on pharmaceutical firms’ abilities to sustain profit outcomes that are above those earned by competing firms. The analysis, which is situated within the U.S. pharmaceutical industry, finds support for the expected relationship between high innovative propensity and sustained superior profitability, but no support for a link between persistence and the ability to avoid competition. Copyright © 1999 John Wiley & Sons, Ltd.